Δοκιμές εξόλκευσης ράβδων τιτανίου από την τοιχοποιία και μέλη των ορθομαρμαρώσεων για την εύρεση ακαμψίας των συνδέσμων στο πλαίσιο της ολοκληρωμένης μελέτης προστασίας του Ιερού Κουβουκλίου του Παναγίου Τάφου στα Ιεροσόλυμα - Κούκουρας, Ευάγγελος (Σχολή Αρχιτεκτόνων Μηχανικών, 2017)
The aim of this research is the determination of stiffness, strength and failure mechanisms of titanium anchors with which the outer cladding of the Holy Aedicule is retained in masonry. The first chapter discusses the methodology of the diagnostic study applied to monuments as well as the criteria for selecting the operations and their techniques. The second chapter summarizes the current state of the monument and presents the structural problems. Moreover, it is mentioned the interventions and the criteria of the selection. The third chapter analyzes the replacement of historical anchors of Komnenos with modern ones. The expected characteristics of the anchors are calculated theoretically and then the correctness of calculations is confirmed with a series of experiments carried out at the project site. The fourth and fifth chapter presents the pull-out tests and discussed the results. Additionally, the types of anchorage that were finally selected and applied on the monument are presented and also the forces applied to them in case of earthquake are calculated. In the sixth chapter is presented the proposed procedure of installation of the anchors to the monument.